Does pay for performance improve patient outcomes in a national health service? results from the WHiTE multicentre hip fracture cohort - Griffin, X; Achten, J; Parsons, N; WHiTE Collaborators (British Editorial Society of Bone and Joint Surgery, 2021)
Aims: The aim of this study was to determine whether national standards of best practice are associated with improved health-related quality of life (HRQoL) outcomes in hip fracture patients.